Development of long-circulating lapachol nanoparticles: formation, characterization, pharmacokinetics, distribution and cytotoxicity. Issue 50 (14th August 2020) - Chen, Qunying; Bai, Lu; Zhou, Xuelin; Xu, Pingxiang; Li, Xiaorong; Xu, Huanli; Zheng, Yuanyuan; Zhao, Yuming; Lu, Shousi; Xue, Ming
Abstract : LPC-LP is a promising and potential nanoparticle in the treatment of glioma. Abstract : Lapachol is an active compound for the treatment of malignant brain glioma. However, its physicochemical properties limit its clinical application. The purpose of this study is to develop a nano-drug delivery system (LPC-LP) loaded with lapachol (LPC), which remarkably prolongs the half-life in the body, and increases the brain intake, therefore, achieving a better anticancer effect in the treatment of glioma. In order to optimize the formulation of liposomes, an orthogonal design was adopted with entrapment efficiency (EE) as the index. The characterization of the optimized formulation was evaluated in vitro . To assess the safety profile and effect of LPC-LP, a rapid and sensitive ultra-fast liquid chromatography with tandem mass spectrometry (UPLC-MS/MS) method was developed for studying the pharmacokinetics and brain distribution of LPC-LP and LPC. Finally, the cytotoxicity of the two preparations on C6 cells was studied by the MTT assay. The results showed that the average particle size of LPC-LP was 85.92 ± 2.35 nm, the EE of liposomes was 92.52 ± 1.81%, and the charge potential was −40.70 ± 9.20 mV. An in vitro release study showed that the release of lapachol from LPC-LP was delayed compared to LPC, indicating that LPC-LP was a sustained and controlled release system. The UPLC-MS/MS method was fully validated in both plasma and brain tissue according to the Food and Drug Administration (FDA) recommended guidelines, and successfully used for quantification of lapachol in vivo . After intravenous administration, LPC-LP prolonged circulation time of lapachol in the body and increased brain intake. Besides, the MTT results revealed that the IC50 value of LPC-LP on C6 cells significantly decreased, compared with LPC, which further confirmed that LPC-LP enhanced the inhibition of C6 cells and improved the anti-glioma effect. In conclusion, LPC-LP could serve as a promising candidate for the clinical application of lapachol in the treatment of glioma.